Implementasi Pembelajaran IPS Melalui Outing Class Di SDN 2 Sendangmulyo - Yanuanti, Afifah Dini (Peneliti.net, 2024)
One of the important lessons for children's development is social science, which helps children understand how the world functions, including their culture, community and environment. Through this learning, children can gain a better understanding of themselves and their relationships with others, and they can also learn social skills necessary for daily living. One way to apply social studies learning to outing class. In this method, children get hands-on experiences, such as visiting historical places and watching cultural performances. This research uses a qualitative approach, which collects data through in-depth observation and interviews. Researchers found that social science learning can be applied.